Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1081/cbi-200036878
|View full text |Cite
|
Sign up to set email alerts
|

Teen at Work: The Burden of a Double Shift on Daily Activities

Abstract: The purpose of this study was to the evaluate time spent by working and nonworking adolescents on daily activities (work, home duties, school, transportation, other activities, leisure, sleep, and naps). Twenty-seven students, 8 male workers, 8 female workers, 5 male nonworkers, and 6 female nonworkers, ages 14-18 yrs participated in the study. They attended evening classes Monday-Friday (19:00-22:30h) in a public school in the city of São Paulo, Brazil. The students answered a comprehensive questionnaire on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
0
25
1
8
Order By: Relevance
“…Several Latin American studies aiming to evaluate work conditions and health outcomes among working adolescents have earlier been published (3)(4)(5)(6)(7)(8). Results from these studies show that adolescents who work and attend evening classes wake up earlier and have a shorter nocturnal sleep duration and shorter total sleep duration during the week than nonworking students.…”
mentioning
confidence: 60%
“…Several Latin American studies aiming to evaluate work conditions and health outcomes among working adolescents have earlier been published (3)(4)(5)(6)(7)(8). Results from these studies show that adolescents who work and attend evening classes wake up earlier and have a shorter nocturnal sleep duration and shorter total sleep duration during the week than nonworking students.…”
mentioning
confidence: 60%
“…68 Another contributing factor is working status, with adolescents who engage in employment displaying shorter sleep durations and increased daytime sleepiness compared to their non-working peers. [69][70][71] Fischer et al 71 also found shorter adolescent sleep duration to be related to increased smoking and drinking behavior. Many of these environmental and behavioral factors relate to social and emotional maturation and increased independence, and are likely to interact with the biological factors described above in influencing sleep-wake and circadian changes.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…15,17 In addition to biological mechanisms, social and lifestyle factors such as heavy academic load, after-school activities or jobs, screen time, and caffeine consumption also contribute to adolescents' later bedtimes. [18][19][20] Because most adolescents in the United States start school before 8:30 am, 21,22 it is not surprising that the average teen experiences a chronic sleep debt. 23 Numerous reports suggest that delaying school start time (SST) improves sleep patterns.…”
Section: Introductionmentioning
confidence: 99%